Transcriptional Modulation of Penicillin-Binding Protein 1b, Outer Membrane Protein P2 and Efflux Pump (AcrAB-TolC) during Heat Stress Is Correlated to Enhanced Bactericidal Action of Imipenem on Non-typeable Haemophilus influenzae - Cherkaoui, Abdessalam; Diene, Seydina M.; Fischer, Adrien; Leo, Stefano; François, Patrice; Schrenzel, Jacques (Frontiers in Microbiology, 2018)
Objective: The purpose of the present study was to investigate the penicillin binding proteins, drug influx and efflux modulations during heat stress and their effects on the bactericidal action of imipenem on nontypeable Haemophilus influenzae (NTHi). Methods: The two NTHi clinical isolates (GE47 and GE88, imipenem MICs by E-test >32 µg/mL) examined in this study were collected at Geneva University Hospitals. The imipenem killing activity was assessed after incubation of the NTHi strains at either 37 or 42°C for 3h with increasing concentrations of imipenem. The detection of penicillin binding proteins (PBPs) was carried out by Bocillin-FL. Global transcriptional changes were monitored by RNA-seq after pre-incubation of bacterial cells at either 37 or 42°C, and the expression levels of relevant target genes were confirmed by qRT-PCR. Results: Quantitation of NTHi viable cells after incubation with 0.25µg/mL of imipenem for 3h revealed more than a two-fold decrease in GE47 and GE88 viable cells at 42°C as compared to 37°C. Transcriptome analysis showed that under heat stress conditions, there were 141 differentially expressed genes with a |log2(fold change)| >1, including 67 up-regulated and 74 down-regulated genes. The expression levels of ponB (encoding PBP1b) and acrR (regulator of AcrAB-TolC efflux pump) were significantly increased at 42°C. In contrast, the transcript levels of ompP2 (encoding the outer membrane protein P2) and acrB gene (encoding AcrB) were significantly lower under heat stress condition. Conclusions: This study shows that the transcriptional modulation of ponB, ompP2, acrR, and acrB in the heat stress response is correlated to enhanced antimicrobial effects of imipenem on nontypeable Haemophilus influenzae.